Strain distributions and their influence on electronic structures of WSe2–MoS2 laterally strained heterojunctions - Zhang, Chendong; Li, Ming-Yang; Tersoff, Jerry; Han, Yimo; Su, Yushan; Li, Lain-Jong; Muller, David A.; Shih, Chih-Kang (Nature nanotechnology, 2018)
Monolayer transition metal dichalcogenide heterojunctions, including vertical and lateral p–n junctions, have attracted considerable attention due to their potential applications in electronics and optoelectronics. Lattice-misfit strain in atomically abrupt lateral heterojunctions, such as WSe 2 –MoS 2 , offers a new band-engineering strategy for tailoring their electronic properties. However, this approach requires an understanding of the strain distribution and its effect on band alignment. Here, we study a WSe 2 –MoS 2 lateral heterojunction using scanning tunnelling microscopy and image its moiré pattern to map the full two-dimensional strain tensor with high spatial resolution. Using scanning tunnelling spectroscopy, we measure both the strain and the band alignment of the WSe 2 –MoS 2 lateral heterojunction. We find that the misfit strain induces type II to type I band alignment transformation. Scanning transmission electron microscopy reveals the dislocations at the interface that partially relieve the strain. Finally, we observe a distinctive electronic structure at the interface due to hetero-bonding. Mapping a moiré pattern in a lateral lattice-mismatched WSe 2 –MoS 2 heterojunction enables determination of the full strain tensor and the study of strain-induced electronic properties.